2021
DOI: 10.1172/jci143771
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal motility disorders in neurologic disease

Abstract: Conflict of interest: MC owns equity in Enterin Inc., which is developing ENT-01 for Parkinson disease. In the past year, MC has received research grants from Allergan (eluxadoline for bile acid diarrhea), Takeda (TAK-954 for gastroparesis), and ILSI North America (intestinal permeability). MC has submitted patent applications for (a) capsule for colonic transit by scintigraphy (publication number US5827497A); (b) 13C-mannitol for permeability measurements (publication number US20190145953); and (c) obesity-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 149 publications
(122 reference statements)
0
79
0
4
Order By: Relevance
“…In line with this view, other studies performed on SAMP8 and AβPP/PS1 transgenic AD mouse models observed the accumulation of intestinal Aβ and amyloid precursor protein, enteric inflammation, mitochondrial dysfunction along with enteric glial activation and gut dysbiosis in the early stages of AD before the full development of brain pathology ( Joachim et al, 1989 ; Puig et al, 2015 ; Piccarducci et al, 2019 ; Pellegrini et al, 2020 ). Bowel motor disturbances in AD patients contribute significantly to AD morbidity and complicate their clinical management ( Puig et al, 2015 ; Doi et al, 2019 ; Camilleri, 2021 ). In this regard, no specific treatments are currently available to manage gut alterations occurring in such patients and, therefore, the identification of novel pharmacological entities able to prevent or alleviate gut dysfunctions associated with AD represents an area of interest to the scientific community.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this view, other studies performed on SAMP8 and AβPP/PS1 transgenic AD mouse models observed the accumulation of intestinal Aβ and amyloid precursor protein, enteric inflammation, mitochondrial dysfunction along with enteric glial activation and gut dysbiosis in the early stages of AD before the full development of brain pathology ( Joachim et al, 1989 ; Puig et al, 2015 ; Piccarducci et al, 2019 ; Pellegrini et al, 2020 ). Bowel motor disturbances in AD patients contribute significantly to AD morbidity and complicate their clinical management ( Puig et al, 2015 ; Doi et al, 2019 ; Camilleri, 2021 ). In this regard, no specific treatments are currently available to manage gut alterations occurring in such patients and, therefore, the identification of novel pharmacological entities able to prevent or alleviate gut dysfunctions associated with AD represents an area of interest to the scientific community.…”
Section: Introductionmentioning
confidence: 99%
“…The ENS is a complex network of enteric neurons and glia that controls all aspects of GI physiology (Long-Smith et al, 2020; Schneider et al, 2019; Yoo and Mazmanian, 2017) and plays a central role in initiation and progression of enteric neuropathies and diseases of the gut-brain axis (Camilleri, 2021; Niesler et al, 2021; Pesce et al, 2018). Nevertheless, our understanding of the ENS has been disproportionately affected by long standing technical challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Pandysautonomia can affect both sympathetic and parasympathetic nerves, leading to gastrointestinal symptoms. 15 Selective cholinergic dysautonomia can result in gastrointestinal dysmotility and occurs after infection with Epstein-Barr Virus (EBV) or influenza. 15 Idiopathic orthostatic hypotension can be associated with gastrointestinal motor dysfunction, such as fecal incontinence.…”
Section: Discussionmentioning
confidence: 99%